Social Networks as New Business Concept for Enterprises - Raut, Jelena; Mitrović, Slavica; Melović, Boban; Lolić, Teodora (International Journal of Industrial Engineering and Management, 2018)
Social networks provide an excellent opportunity for internet advertising and promotion in order to improve business operations. The aim of this paper is to demonstrate the possibility of adequate use of social networks for the establishment, expansion and quality functioning of companies in the area of online trading. Subsequently, the paper presents a concept, a PHP-based web application, used by large trading systems, which is designed and adapted for use in small companies in their everyday operation. Finally, all measures for improving the existing system are presented using a specific case study, through integration with systems owned by company’s permanent suppliers, in order to save time and increase the accuracy of procurement, which takes place on a weekly basis. Article history: Received (14.06.2018); Revised (30.08.2018); Accepted (05.09.2018)